Adipose tissue-liver cross-talk: a route to hepatic dysfunction in pregnant women with obesity - Sousa, Diana Isabel Teixeira de (2024)
Obesity during pregnancy has been escalating, becoming a huge problem that poses consequences not only for the health of the offspring but also for the maternal well-being. Women's adipose and hepatic tissue metabolism undergoes significant changes during the gestational period. During pregnancy, obesity is a primary instigator of steatosis, increasing the risk of non-alcholic fatty liver disease (NAFLD), now recognized under the updated nomenclature metabolic dysfunction-associated steatotic liver disease (MASLD). Pregnant women with obesity present higher levels of free fatty acids and glucose, reduction in insulin sensitivity, and adipose tissue endocrine dysregulation. Furthermore, obesity-induced modifications in clock genes and lipid-associated gene expression within adipose tissue disrupt crucial metabolic adaptations, potentially culminating in adipose tissue dysfunction. Thus, the liver experiences increased exposure to free fatty acids through the portal vein. Higher uptake of free fatty acids into the liver disrupts hepatic lipid oxidation while enhances lipogenesis, thereby predisposing to ectopic fat deposition within the liver. This review focuses on the obesity-induced changes during pregnancy in both liver and adipose tissue metabolism, elucidating how the metabolic crosstalk between these two organs can be dysregulated in pregnant women living with obesity.